Isabelline Wheatear (Oenanthe isabellina), a New Species for the Republic of Moldova: A Regional Review of Species Expansion - Mihail Ghilan; Vitalie Ajder; Silvia Ursul; Emanuel Ștefan Baltag (Land)
Increasing temperatures due to climate change can favor more thermophilic species, allowing them to expand their territories northward. For the Isabelline Wheatear (Oenanthe isabellina), climate change may facilitate further range expansion as higher temperatures and changing precipitation patterns create more favorable conditions in new areas. The Isabelline Wheatear is a small passerine bird belonging to the Old-World flycatchers. This species’ breeding range extends from temperate southeastern Europe and Asia Minor across arid desert and steppe regions to subtropical northern areas. Its habitat preference includes arid environments characterized by high temperatures, low precipitation, and open spaces. Field observations were collected over four breeding seasons (2021–2024) through the Common Bird Monitoring scheme and occasional observations. Prediction models also incorporated observations from scientific literature and online databases for covering neighboring areas in Ukraine and Romania. Using Maxent species distribution models (SDMs) and all presence locations and bioclimatic variables, predicted modes were built to identify new suitable areas for the Isabelline Wheatear. Most of the predicted range lies close to the Black Sea coast, in southeastern and southwestern Moldova. According to available data, the Isabelline Wheatear inhabits the southern third of Moldova. Fifteen locations have been identified as hosting breeding populations in proper habitats. Until 2021, the Isabelline Wheatear was considered a recent cryptic or overlooked breeding species in Moldova. This is likely due to several factors, including its recent entry into the country’s territory, potentially from two different directions at different times. The new data and predictive models provide valuable insights into the current distribution and future expansion potential of this species, underscoring the dynamic nature of avian responses to climate change.